Hacking work : breaking stupid rules for smart results - Jensen, Bill, 1955-; Klein, Josh, 1974- (New York : Portfolio Penguin, 2010)
'... Reveals powerful technological and social hacks and shows readers how to apply them to sidestep bureaucratic boundaries and busywork'--Jacket.
Woot! -- Saving business from itself, one bad act at a time -- You were born to hack -- What's new, what's not, what's the most common hack? -- Get hacking -- Breaking stupid rules for smart results -- Five hacks everyone should do -- Do no harm -- Whoa -- What's broken now -- What's ahead -- The elephant in the room -- Making a difference -- Dear Boss -- Stop the madness now -- Hacking the world.
Includes bibliographical references and index.
Keywords: Organizational effectiveness; Creative thinking; Problem solving